Introducing the Bidimensional Model of Hope and its conceptual and methodological utilities - Leshem, Oded Adomi; Halperin, Eran (Frontiers in Psychology, 2024)
What is hope, and how can we measure it? These questions have occupied the minds of hope scholars across disciplines. This article outlines a comprehensive approach to understanding hope: the Bidimensional Model of Hope. Building on the standard definition of hope, the bidimensional model explores hope as the intersection between wishes (desires, aspirations) and expectations (assessment of possibility). Hope is thus located on a bidimensional plane with two perpendicular axes; one corresponds to the levels of wishes to achieve an outcome, and the second to the levels of expectations of achieving the outcome. We claim that the bidimensional approach is comprehensive enough to include existing definitions of hope while being parsimonious, versatile, and applicable to many contexts, including those where the hoped-for outcome is beyond people's actual or perceived control. We show the model's theoretical and methodological utility and its use in existing qualitative and quantitative research on hope in the context of intractable international conflicts. We end with suggesting pathways for developing and applying the Bidimensional Model of Hope to assist hope research in a variety of contexts and disciplines.